Estimation of Hematological Parameters of Disease Severity in Iraqi Patients with COVID-19 - Mahmood, Zainab S.; Fadhil, Hula Y.; Ad′hiah, Ali H (Iraqi Journal of Science, 2021)
Coronavirus disease 2019 (COVID-19) is a systemic disease with a substantial impact on the hematopoietic system and hemostasis. Neutrophilia is an early indicator of SARS-CoV-2 infection, while lymphopenia acts as a biomarker of the severity of infection, and the neutrophil-to-lymphocyte ratio (NLR) is the main indicator of cytokine storms. Thus, this study aimed to provide local data about hematological parameters among COVID-19 patients and estimate their correlation with viral load and other factors in severe cases. A total of 99 nasopharyngeal swabs and whole blood specimens were collected from individuals suspected with COVID-19 between October and December 2020. Samples were tested by real time reverse transcriptase polymerase chain reaction (rRT-PCR) assay, COVID-19 IgG and IgM antibody tests, beside hematological analysis. The results showed a significant increase in neutrophils count and NLR, correlated with the severity of the disease Patients at older ages who are suffering from some comorbidity like hypertension and diabetes are at elevated risk to develop more severe disease outcome. The findings demonstrated a higher neutrophils count and higher death ratio in older ages. Also, the results suggest that NLR could be employed as a useful biomarker and potential prognostic tool supporting the importance of laboratory records in assessing case severity and disease progression.